In-hospital informal caregivers' needs as perceived by themselves and by the nursing staff in Northern Greece: A descriptive study - Georgiadou Charikleia; Areti Tsaloglidou; Psychogiou Maria; Sgantzos Markos; Raftopoulos Vasilios; Lavdaniti Maria; Serpanou Ismini; Sapountzi-Krepia Despina (BMC, 2011)
Abstract Background Informal care is common in many countries, especially in Greece, where families provide care in hospitals. Health education and informational needs are important factors for family members which are often underestimated by nursing staff. The aim of this study was to compare the perceptions of the nurses and the in-hospital informal caregivers about the in-hospital informal caregivers' knowledge and informational needs, as well as the factors that influence these perceptions. Methods This was a non-experimental descriptive study conducted in three general hospitals in Greece. The sample consisted of 320 nurses and 370 in-hospital informal caregivers who completed questionnaires. Descriptive statistics were analyzed using t-tests; group comparisons were conducted using ANOVA. Results The score of the questionnaire for health education and informational needs was significantly greater for informal caregivers (57.1 ± 6.9 and 26.6 ± 2.8) than for nurses (53.4 ± 5.7 and 22.4 ± 3.1) (p < 0.001). For the nursing staff, the factors that influence the informational needs of patients' caregivers were level of education and working experience, while for the caregivers the level of education was independently associated with the score for the health education needs. Finally, age, marital status, and level of education of informal caregivers' were independently associated with informational needs. Conclusions The in-hospital informal caregivers perceived that they have more educational and informational needs than the nurses did. The findings of this study also show that the nursing staff has to identify the needs of in-hospital informal caregivers in order to be able to meet these needs.